Effects of a parent-administered exercise program in the neonatal intensive care unit: Dose does matter-a randomized controlled trial - Øberg, Gunn Kristin; Girolami, Gay L; Campell, Suzann K.; Ustad, Tordis; Heuch, Ivar; Jacobsen, Bjarne K.; Kaaresen, Per Ivar; Aulie, Vibeke Smith; Jørgensen, Lone (Physical Therapy, 2020)
This is a pre-copyedited, author-produced version of an article accepted for publication in Physical Therapy following peer review. The version of record Øberg gk, Girolami GL, Campell, Ustad T, Heuch I, Jacobsen bk, Kaaresen pi, Aulie VS, Jørgensen l. Effects of a parent-administered exercise program in the neonatal intensive care unit: Dose does matter-a randomized controlled trial . Physical Therapy. 2020;100(5):860-869 is available online at: https://doi.org/10.1093/ptj/pzaa014. Background - Despite the risk of delayed motor development in infants born preterm, knowledge about interventions in the neonatal intensive care unitt (NICU) and the effects of dosing is sparse. Objective - The objectives of this study were to examine the effectiveness of a parent-administered exercise program in the NICU on motor outcome at 3 months corrected age (CA) and the effect of dosing on motor performance. Design - This was a randomized clinical trial. Setting The study was conducted at 3 university hospitals in Tromsø, Trondheim, and Oslo, Norway. Participants - A total of 153 infants with gestational age <32 weeks at birth were randomly assigned to intervention or control groups. Intervention - A 3-week parent-administered intervention designed to facilitate movements in preterm infants was performed in the NICU. Parents were asked to administer the intervention 10 minutes twice a day. Measurements - Test of Infant Motor Performance (TIMP) was used to assess short-term outcome at 3 months CA. Results - No significant difference in the TIMP z-score was found between intervention and control groups at follow-up 3 months CA, but a significant positive relationship was found between total intervention dose and TIMP z-scores. The adjusted odds of having a clinical z-score < 0 at 3 months CA was about 6 times higher for infants with less than median intervention time than for infants with a longer intervention time. Limitations - The number of infants born before 28 weeks was small. A spillover effect in favor of the ...